Correlation between uterine microbiota and pregnancy outcomes of embryo transfer in overweight and obese women - Ying Yan; Ying Li; Lingling Wu; Yuxuan Zhang; Hong Guo; Yazhong Ji (Frontiers in Cellular and Infection Microbiology)
ObjectiveCurrently, it has been reported that uterine microbiota affected pregnancy outcomes in assisted reproductive technology, but little was known in obese women. Thus, this study aims to explore how body weight affects pregnancy outcomes by comparing the differences in uterine microbiota between women of normal weight and those with obesity or overweight.MethodsThe study included 45 embryo transfer cycles. Patients were divided into two groups based on body mass index (BMI): normal-weight group, BMI ≤23.9 kg/m² (Con group, n=31) and obesity/overweight group, BMI >23.9 kg/m² (OwOb group, n=14). Microbial samples were collected from the catheter tips and analyzed using RNA Ribosomal 16S.ResultsIn 45 women, the β-human chorionic gonadotropin (β-hCG) positivity rate and clinical pregnancy rate 10-12 days after embryo transfer were higher in the Con group. At the genus level, the relative abundance of Lactobacillus in the Con group was 2.2 times higher than that in the OwOb group. The Alpha diversity in the OwOb group was significantly higher than in the Con group (p=0.028). After regrouping based on β-hCG results 10-12 days post-transfer, in the Con-negative group (the group with negative β-hCG in the Con group, n=16) the relative abundances of pathogenic bacteria such as Klebsiella (p<0.001), Parasutterella (p=0.004), Dialister (p=0.01), and Gardnerella (p=0.029) were significantly higher than in the Con-positive group (the group with positive β-hCG in the Con group, n=15).ConclusionOverweight and obese women possess a distinct uterine microbiota, characterized by a lower relative abundance of Lactobacillus and an increased relative abundance of pathogenic bacteria, along with specific genera strongly associated with obesity. In individuals with higher BMI, pathogenic bacteria are more likely to impair endometrial receptivity, ultimately leading to adverse pregnancy outcomes. Therefore, modulating the uterine microbiota in overweight/obese women may improve assisted reproductive technology success rates.